Pengaruh Pendapatan Orang Tua Terhadap Motivasi Belajar Siswa Mata Pelajaran IPA (BIOLOGI) Kelas VII di SMP NEGERI 20 Sigi - Karima, Nur; Bialangi, Mursito S.; Febriani, Vita Indri; Windarsih, Yulia; Rafiqah, Rafiqah; Jamhari, Muhammad (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to describe the influence of parental income on students' learning motivation. This study uses a descriptive qualitative approach. The subjects of this study consisted of 30 students in grade VII. The results showed that the majority of students came from families with low incomes, and this had an impact on students' low learning motivation. The level of parental income influenced the learning motivation of students in the subject of science (Biology) in grade VII at SMP Negeri 20 Sigi. The researcher found several students whose parents had low incomes so that it influenced the students' learning motivation, from the 30 samples that the researcher used, there were 26 students with low incomes with incomes <Rp.500,000 and those with high incomes were 4 students with incomes of Rp. 1,000,000 - Rp. 1,999,999. The average student learning motivation only reached 36%, which is included in the very low category. Internal factors (31%) and external factors (42%) both play a role in decreasing students' learning motivation. Interventions such as scholarships and support from parents and schools are needed to increase students' enthusiasm for learning. Thus, it can be concluded that the learning motivation of class VII students at SMP Negeri 20 Sigi is very low.